Birthplace in Australia: Processes and interactions during the intrapartum transfer of women from planned homebirth to hospital. (February 2018) - Fox, Deborah; Sheehan, Athena; Homer, Caroline
Abstract: Objective: the aim of the study was to explore the views and experiences of women, midwives and obstetricians on the intrapartum transfer of women from planned homebirth to hospital in Australia. Design: a Constructivist Grounded Theory approach was taken, to conceptualise the social interactions and processes grounded in the data. Setting: urban and regional areas in four states of south-eastern Australia. Participants: semi-structured qualitative interviews were conducted with 36 women, midwives and obstetricians who had experienced an intrapartum homebirth transfer within three years prior to the interview. Interviews were audio recorded and transcribed verbatim. Findings: women who were transferred to hospital from a planned homebirth made physical and psychological journeys out of their comfort zone, as they faced the uncertainty of changing expectations for their birth. The trusting relationship between a woman and her homebirth midwife was crucial to women's sense of safety and well-being in hospital. Midwives and obstetricians, when congregating in the hospital birthing rooms of transferred women, also felt out of their comfort zones. This was due to the challenges of converging with others who possessed conflicting paradigms of safety and risk in birth that were at odds with their own, and adapting to different routines, roles and responsibilities. These differences were derived from diverse professional, social and personal influences and often manifested in stereotyping behaviours and 'us and them' dynamics. When midwife-woman partnerships were respected as an inclusive part of women's care, collaboration ensued, conflict was ameliorated, and smooth transfers could be celebrated as successes of the maternity care system. Key conclusions: supporting woman centred care in homebirth transfers means acknowledging the social challenges of collaborating in the unique context of a transferred woman's hospital birthing room. Understanding the power of the midwife-woman partnership, and its value to the health and well-being of each woman and her baby, is key to facilitating a successful transfer. Implications for practice: the midwife-woman partnership played a central role in providing the necessary support and advocacy for women transferred out of their comfort zone. When midwives worked together in an integrated system to provide the necessary care and support for women who were transferred, greater levels of collaboration emerged and women's perceptions of their quality of care was high. In practice, this meant health professionals respecting each other's roles, responsibilities and expertise, and ameliorating 'us and them' dynamics. Highlights: During homebirth transfer, women and caregivers transferred out of their comfort zones. Understanding the value of the midwife-woman partnership was key to woman centred care. Collaborative care meant midwives respecting each other's expertise, roles and responsibilities. Smooth transfers should be celebrated as a success of the system, rather than as failed homebirths.